A COMPARATIVE ANALYSIS OF OCCASIONALISMS AND NEOLOGISMS: FORMATION, USAGE, AND LIFESPAN IN THE EVOLUTION OF LANGUAGE (Лучшие интеллектуальные исследования, 2025)
Abstract: Language is a constantly evolving system that adapts to changes in society, technology, and culture. Both occasionalisms and neologisms, which add new lexical words, are examples of the mechanisms behind this evolution. Though they are frequently used interchangeably, these phrases have different purposes and unique traits. In order to differentiate occasionalisms from neologisms, this article will look at their meanings, formation processes, usage, and possibility for universal lexicon acceptance.